2015
DOI: 10.15850/amj.v2n4.661
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception on Ideal Age of Marriage and Childbearing

Abstract: Background: Early-age marriage is still common in Indonesia, especially in the rural areas. There are many negative effects of the marriage; the young brides may get lower education, lower social status, minimum reproduction control, higher maternal mortality, higher domestic violence rate and others. Thus, this study is conducted to identify the students' perception on the ideal age of marriage and childbearing. Methods: A cross-sectional descriptive study was conducted from June to September 2013 in Jatinang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Studies from other settings have shown different results. A study from Indonesia revealed that 74% of the student participants considered 19–24 years of age the ideal age range for marriage for women, and 68% considered 25–30 years the perfect age range for men to marry [ 17 ]. In a study among Syrian refugees, half of the respondents believed that the average ideal age of marriage for girls is less than 18 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other settings have shown different results. A study from Indonesia revealed that 74% of the student participants considered 19–24 years of age the ideal age range for marriage for women, and 68% considered 25–30 years the perfect age range for men to marry [ 17 ]. In a study among Syrian refugees, half of the respondents believed that the average ideal age of marriage for girls is less than 18 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%